Parenting Orang Tua dalam Membentuk Identitas Gender Anak dalam Perspektif Psikologi - Finanin Nur Indana (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Parents play a crucial role in introducing and shaping children’s gender identity from an early age. Gender identity is an essential aspect of psychological development that is closely related to the formation of behavior patterns, social attitudes, and personality development in later life. Within the family context, both fathers and mothers have complementary psychological roles in supporting children’s gender development. Mothers are generally more involved in daily caregiving and the fulfillment of children’s physical and emotional needs, while fathers tend to play a more prominent role in social interaction, play activities, and reinforcing discipline as well as adherence to prevailing cultural norms. Parenting practices, whether consciously or unconsciously applied, significantly influence how children understand gender roles, express themselves, and construct their personal identities. Therefore, appropriate, balanced, and developmentally sensitive gender identity introduction is essential to prevent role confusion and potential psychological difficulties in the future. This article aims to examine the role of parents in shaping children’s gender identity from a psychological perspective, emphasizing the importance of responsive, educative parenting that aligns with children’s developmental stages and cultural values.